Evaluation of liver function test in malaria positive cases in tertiary care hospital of Bareilly - Agarwal, Ajay Kumar; Katiyar, Ghanshyam Dass; Khan, Swati; Chaudhary, Bharat Chand; Singh, Arun; Sharma, Mahendra (International Journal Of Community Medicine And Public Health, 2020)
Background: Malaria is a life-threatening disease. The aim of this study was to evaluate liver function test in malaria positive cases. Methods: A cross sectional study was done to find out changes in liver function test in malaria positive cases. Study was done in Central Pathology Lab, RMCH, Bareilly, Uttar Pradesh. Blood samples were collected in EDTA and plain vacutainer tube. Blood smear was examined for malaria parasite within RBCs. Malaria rapid test was done for detection of Plasmodium species and liver function test was done for effect of malaria. Results: In this study it was found that maximum malaria positive cases (25.50%) in 21-30 years age group. and in males (22.56%) in 11-20 years age group and in females (34.75%) in 21-30 years age group. Maximum cases of P. vivax (27.66%) in 21-30 years age group, P. falciparum (33.33%) in 21-30 and 41-50 years age group and mixed malarial infection (21.92%) in 31-40 years age group was found maximum P. vivax cases (51.06%) and mixed malarial infection (65.75%) in male and maximum P. falciparum (66.67%) in female was found. Maximum above normal limit serum bilirubin (63.75%), direct serum bilirubin (67.93%), SGPT (38.45%), SGOT (70.52%) and ALP (48.01%) was found in malaria positive cases. Maximum deranged serum bilirubin (83.33%), direct bilirubin (100.00%), SGOT (100.00%), ALP (83.33%) was found in P. falciparum and maximum deranged SGPT (50.68%) was found in mixed infection. Conclusions: Malaria remains a major health problem in developing countries it affects the liver function test which helps in management of malaria patient.